Nonsecretory Multiple Myeloma Presenting as an Intestinal Tumor - Diana Triantafyllopoulou; Stuart Mellor; Catherine Cargo; Ioannis Gkikas; Jagdish Adiyodi; Ayub Ali Bin; Neil Sahasrabudhe; Margaret Rokicka (Case Reports in Hematology)
We report a case of a 43-year-old Caucasian man who presented with colicky abdominal pain and microcytic hypochromic anemia. The patient underwent a colonoscopy where a tumor was seen in the ascending colon; histology showed plasmacytoma of the colon. From the protein electrophoresis, no monoclonal band or free light chains were detected nor was urinary Bence Jones protein present. A bone marrow biopsy showed plasma cell myeloma. To the best of our knowledge, this is the first case of nonsecretory multiple myeloma presenting as plasmacytoma of the colon.